2009
DOI: 10.1016/j.ccr.2009.01.019
|View full text |Cite|
|
Sign up to set email alerts
|

MDM2-Dependent Downregulation of p21 and hnRNP K Provides a Switch between Apoptosis and Growth Arrest Induced by Pharmacologically Activated p53

Abstract: We have previously identified the p53-reactivating compound RITA in a cell-based screen. Here, using microarray analysis, we show that the global transcriptional response of tumor cells to RITA is p53 dependent. Pathway analysis revealed induction of the p53 apoptosis pathway, consistent with apoptosis being the major response to RITA in cancer cells. We uncovered that MDM2 released from p53 by RITA promotes degradation of p21 and the p53 cofactor hnRNP K, required for p21 transcription. Functional studies rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
109
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(120 citation statements)
references
References 37 publications
10
109
0
1
Order By: Relevance
“…Conversely, RITA reduced p21 expression, consistent with what was previously reported in other cell lines 19 ( Fig. 2B).…”
Section: P53-reactivating Agents Affect Mesothelioma Cell Viabilitysupporting
confidence: 82%
See 3 more Smart Citations
“…Conversely, RITA reduced p21 expression, consistent with what was previously reported in other cell lines 19 ( Fig. 2B).…”
Section: P53-reactivating Agents Affect Mesothelioma Cell Viabilitysupporting
confidence: 82%
“…39,40 Treatment with nutlin-3, instead, caused a cell cycle arrest in mesothelioma cell lines carrying wt p53, whereas no arrest was achieved in cell lines carrying mutant p53. As described for other tumor types, 19 nutlin-3-induced arrest seems to rely on the upregulation of the p53 target p21. Consistently, we found that nutlin-3 was able to cause cell cycle arrest only in p53 wt cells concomitantly to p21 induction, whereas IST-MES 2 and NCI-H2452, owing to a mutated p53, did not express p21 following nutlin-3 treatment and did not show cell cycle arrest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our group has identified p53-reactivating compound RITA (reactivation of p53 and induction of tumor cell apoptosis) (23). RITA binds the p53 N-terminal domain and disrupts the interaction with its negative regulator MDM2, which results in p53 activation and induction of apoptosis (23,24). 5 Notably, we showed that RITA activates p53 in cells expressing oncogenes, whereas the effect in non-transformed cells is almost negligible (23,25).…”
mentioning
confidence: 97%